AlAndalus, a shining example - Abd Razak, Dzulkifli (2006)
They were remarks bound to infuriate Muslims, especially when the fury over the infamous Danish caricatures is still raw on their minds. Worse, it was a passage from someone who in all probability was an adversary of Islam. Pope Benedict XVI had cited the Byzantine emperor, Manuel Paleologos II. Manuel was the man who had to flee the Ottoman court after being forced to go as an honorary hostage to the court of the Ottoman Sultan Bayezid I, the sultan who besieged Constantinople from 1394 to 1402. Why indeed had the pope quoted him? Interestingly enough, the 14th century marked a time of Renaissance Europe. A time Europe was just emerging from centuries of poverty and social strife, a period better known as the Dark Ages.